Nexus Between Working Capital Management and Sectoral Performance - Suman Talreja; Farhan Ahmed; Raza Ali (Faculty of Economic and Business, 2018)
This study aims to examine the impact of aggressive working capital factors/policies on firms’ performance to improve the financial health. Random and Fixed Effect models estimated by taking annual data of two major sectors: automobile and food sectors from 2006 to 2016. According to the findings, aggressive investment factor/policy (AIF) has a negative impact on gross operating income (GOI) in both sectors while aggressive financing factor/policy (AFF) has an adverse effect on GOI in the food sector and positive impact on GOI in the automobile sector. The results of this study should be of great importance to investors, creditors, and financial analysts, especially after the global financial crisis and the collapses of giant organizations worldwide.DOI: 10.15408/ess.v8i1.7075